FTIR laboratory measurement of He I spectra in the 6.5–14 µm spectral range: Transitions involving f, g, h, and i states. (March 2021) - Civiš, S.; Kubelík, P.; Zanozina, E.M.; Pastorek, A.; Chernov, V.E.; Ferus, M.; Chilukoti, Ashok; Naskidashvili, A.V.
Highlights: 47 new He I lines in the 700–5800  cm − 1 range not observed previously. Experimental energies of 6 h, and 7 h, 7 i He Rydberg levels. Time-resolved high resolution Fourier transform emission infrared spectroscopy. Graphical abstract: Abstract: Time-resolved infrared emission spectra of atomic helium have been measured using a high-resolution Fourier transform spectrometer in the spectral range of 700–15000 cm − 1 with a maximum resolution of 0.01 cm − 1 . A total of 74 spectral lines have been observed, of which 47 lines are detected for the first time. Most of the observed transitions are from highly excited levels ( n = 8, 7 and 6). The time profiles of the spectral line's emission intensities observed under the current experimental conditions have been plotted, and the decay times have been obtained. The level energy values are extracted from the list of spectral lines, and their consistency is justified by the obtained ionization potential of the He atom and the dipole polarizability of He + .